REGENERASI PENGUKIR MUDA DALAM KEBERLANJUTAN INDUSTRI SENI UKIR DI DESA MULYOHARJO, KECAMATAN JEPARA, KABUPATEN JEPARA (Universitas Negeri Semarang, 2022)
In order to maintain the existence of the carving art industry, it is necessary to regenerate young carvers for the sustainability of the Jepara carving industry. The aims of this research are to find out the factors that hinder the regeneration process of young carvers and find out solutions to overcome the problems that arise in the sustainability of the carving art industry.This research used a qualitative-descriptive research method. Data collection techniques in this research are observation, interviews and documentation. Based on the results of the research conducted, it is known that: Factors that hinder the regeneration process of young carvers are family factors, educational factors, economic factors and social factors.The solution to overcome the problems that arise is to increase the introduction of carving through the realm of education and improve the marketing strategy of carving. Demi mempertahankan eksistensi industri seni ukir, maka perlu dilakukan regenerasi pengukir muda dalam keberlanjutan industri seni ukir Jepara. Tujuan dalam penelitian ini adalah mengetahui faktor-faktor yang menghambat proses regenerasi pengukir muda dan mengetahui solusi untuk mengatasi permasalahan yang muncul dalam keberlanjutan industri seni ukir. Penelitian ini menggunakan metode penelitian kualitatif-deskriptif. Teknik pengumpulan data dalam penelitian ini adalah observasi, wawancara dan dokumentasi. Hasil penelitian yang dilakukan diketahui bahwa: Faktor-faktor yang menghambat proses regenerasi pengukir muda adalah faktor keluarga, faktor pendidikan, faktor ekonomi dan faktor sosial. Solusi mengatasi permasalahan yang muncul yaitu meningkatkan pengenalan ukir melalui ranah pendidikan dan meningkatkan strategi pemasaran ukiran.